(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Conservation tillage system offers numerous benefits over intensive tillage system. This experiment was conducted on conservation tillage using zero tilldrill, power tiller operated seeder (PTOS) and bed planter along with farmers practice of tillage by rotary tiller under different irrigation levels at Wheat Research Centre (WRC), Nashipur, Dinajpur. Irrigation water was applied by 5 irrigation levels at different growth stages of the crop. The irrigation levels were I0 (No irrigation), I1 (17-21 DAS), I2 (17-21 DAS + 50-55 DAS). I3 (17-21 DAS+ 50-55 DAS + 75-80 DAS), and I4 (17-21 DAS + 35-40 DAS + 50-55 DAS + 75 80 DAS). It was observed that the sowing cost was reasonably reduced than that of the farmer’s practice. Seasonal water use was less in PTOS than other tillage methods. Grain yield was significantly affected by tillage methods. The higher grain yield was found from PTOS, bed planting, and zero tillage than that of farmer’s practice. There was no significant difference within the interaction effect of tillage methods and irrigations. The effect of irrigation level was found highly significant on grain yield. Water use efficiency increased with decrease of irrigation water use and decreased with increase of irrigation. Average yields in all tillage methods under I1, I2, I3, and I4 irrigation levels were found to increase by 33, 43, 52, and 51 percent, respectively, compared to that of I0. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11172 Bangladesh J. Agril. Res. 37(1): 27-37, March 2012